Caliphs and kings : the art and influence of Islamic Spain - Ecker, Heather.
"Al-Andalus (Islamic Spain), like no other region of the Islamic world evokes a nostalgic perception of a lost paradise : For many, it provides a model of medieval cultural and religious tolerance, intellectual endeavor, and artistic excellence. Caliphs and Kings : The Art and Influence of Islamic Spain explores the magnificent artistic achievements of al-Andalus from the seventh to fifteenth centuries, and its lasting influence on European Christiandom and Jewry." "Caliphs and Kings celebrates the centenary anniversary of The Hispanic Society of America, a unique institution dedicated to the study of the cultural and artistic traditions of Spain. For the first time, the splendid Islamic collections of the society, rarely made available to the public, have been assembled into a single exhibition and volume, supplemented with a small number of objects from the collections of the Smithsonian Institution. Caliphs and Kings provides a window into Islamic empire of the west, and its place in Spanish art and history." -- BOOK JACKET.